2020
DOI: 10.1021/acs.jpcc.0c04755
|View full text |Cite
|
Sign up to set email alerts
|

Photo-Induced State Shifting in 1D Semiconductor Quantum Wires

Abstract: We report on the time-dependent, energetic shifting of quantum-confinement states within photoexcited CdTe quantum wires that were identified by using transient absorption (TA) spectroscopy. The initial photoexcitation promotes an electron to states in the conduction band (CB) and generates a hole in the valence band (VB), and the changes in carrier densities give rise to quantum-state renormalization (QSR). This mechanism is akin to the generation of electron and hole polarons that alter the effective masses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 86 publications
0
28
0
Order By: Relevance
“…3,5,10,18,31−42 These TA data are often complicated and difficult to analyze due to overlapping transient signals. In ref 43, we demonstrated that some of the overlapping inducedabsorption (ΔAbs > 0) and bleach (ΔAbs < 0) signals within the TA data are associated with changes in the electron density distribution induced by photoexcitation; these effects are termed quantum-state renormalization (QSR). 43 In this Letter, we report on the IRD of photoexcited charge carriers within an ensemble of CdTe quantum wires (QWs) characterized using TA spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,5,10,18,31−42 These TA data are often complicated and difficult to analyze due to overlapping transient signals. In ref 43, we demonstrated that some of the overlapping inducedabsorption (ΔAbs > 0) and bleach (ΔAbs < 0) signals within the TA data are associated with changes in the electron density distribution induced by photoexcitation; these effects are termed quantum-state renormalization (QSR). 43 In this Letter, we report on the IRD of photoexcited charge carriers within an ensemble of CdTe quantum wires (QWs) characterized using TA spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In ref 43, we demonstrated that some of the overlapping inducedabsorption (ΔAbs > 0) and bleach (ΔAbs < 0) signals within the TA data are associated with changes in the electron density distribution induced by photoexcitation; these effects are termed quantum-state renormalization (QSR). 43 In this Letter, we report on the IRD of photoexcited charge carriers within an ensemble of CdTe quantum wires (QWs) characterized using TA spectroscopy. 43 The densities of states within the CB and VB of one-dimensional (1D) quantum wires (QWs) contain a continuum associated with the translational motion of the charge carriers along the unconfined dimension.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Semiconductor nanoparticles (NPs) have been extensively studied for their abilities to absorb and emit photons across a tunable range of the electromagnetic spectrum due to quantum-confinement effects. The photoluminescence (PL) quantum yield (Φ PL ) of a sample is a useful metric for assessing the overall quality of the NPs, optimizing synthetic procedures, and improving device efficiencies that incorporate NPs. The Φ PL is the ratio of emission to absorption events.…”
mentioning
confidence: 99%